2017
DOI: 10.1167/17.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic perspective cues enhance depth perception from motion parallax

Abstract: Motion parallax, the perception of depth resulting from an observer's self-movement, has almost always been studied with random dot textures in simplified orthographic rendering. Here we examine depth from motion parallax in more naturalistic conditions using textures with an overall 1/f spectrum and dynamic perspective rendering. We compared depth perception for orthographic and perspective rendering, using textures composed of two types of elements: random dots and Gabor micropatterns. Relative texture motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This may reflect that sensory signals which contribute to perception in natural conditions are not necessarily present in an experiment. For example, in addition to binocular and monocular cues studied here, 3D perception depends on cues such as lighting (shading), self-motion (motion parallax), and ocular cues (blur and accommodation; Buckthought, Yoonessi, & Baker, 2017; de la Malla, Buiteman, Otters, Smeets, & Brenner, 2016; Muryy, Welchman, Blake, & Fleming, 2013; Zannoli, Love, Narain, & Banks, 2016). Recent advances in 3D rendering and display technologies have increased the ability to study perception under more naturalistic conditions, and promise to yield further insights into how individual sensory cues contribute to 3D perception.…”
Section: Discussionmentioning
confidence: 91%
“…This may reflect that sensory signals which contribute to perception in natural conditions are not necessarily present in an experiment. For example, in addition to binocular and monocular cues studied here, 3D perception depends on cues such as lighting (shading), self-motion (motion parallax), and ocular cues (blur and accommodation; Buckthought, Yoonessi, & Baker, 2017; de la Malla, Buiteman, Otters, Smeets, & Brenner, 2016; Muryy, Welchman, Blake, & Fleming, 2013; Zannoli, Love, Narain, & Banks, 2016). Recent advances in 3D rendering and display technologies have increased the ability to study perception under more naturalistic conditions, and promise to yield further insights into how individual sensory cues contribute to 3D perception.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of these studies used 3D monitors for the stereoscopic 3D condition and displayed the same image to both eyes or used 2D monitors for the monoscopic 3D condition. Buckthought et al [ 19 ] showed that dynamic perspective changes enhance depth ordering performance. Therefore, the depth information conveyed through monoscopic 3D inside an HMD which can be freely moved and moved closer and further could provide more helpful depth information when compared to 2D monitors, as the dynamic perspective changes provide depth cues.…”
Section: Related Workmentioning
confidence: 99%
“…This can present as a cue conflict, i.e., when the human visual system is exposed to a visual scene with multiple cues to depth, one of the cues may over-ride the others or combine with them in different strengths [53]. Prior studies [54], [55], [56] involving retinal motion and VR have shown that subjects making use of their head movements perform better in 3DMP tasks. As our framework currently involves using extra-retinal cues viz.…”
Section: A Disabling Head-trackingmentioning
confidence: 99%